Transcriptome analysis of serum biomarker, shared gene signature and pharmacological targets between diabetic cardiomyopathy and nephropathy - Liu, Yang; Chen, Mei; Zhu, Chen; Guo, Daoyu (Biochemistry and biophysics reports, 2025)
Cardio-renal injury frequently coexist in patients with diabetes mellitus. This study aims to explore the serum parameters, shared gene signature, pharmacological targets, and potential candidate compounds of the two major diabetic complications. This study employed a series of analytical methodologies, including omics analysis, bioinformatics analysis, correlation analysis, machine learning, network pharmacology, and molecular docking. External single-cell sequencing dataset was used to investigate the significance of the shared gene signatures in early diabetic nephropathy. HBA1, HBA2, and HBB were identified as shared gene signature that significantly downregulated in both peripheral blood and diabetic kidney glomeruli, but not in diabetic kidney tubuli. PEA15 and TFPI2 were identified shared gene signature that were significantly upregulated in simulated diabetic cardiomyopathy and diabetic kidney tubules, but not in glomeruli. The primary mechanism of diabetic cardiomyopathy is glycolysis and gluconeogenesis, while immune and inflammatory mechanisms contribute to diabetic nephropathy. PEA15 and TFPI2 are associated with glomerular filtration rate (GFR) and serum creatinine levels, and are closely related to programmed cell death processes such as apoptosis and ferroptosis. Machine learning identified core features such as HBB, HBA1, and PEA15. Single-nucleus RNA sequencing analysis identified a high expression of TFPI2 in the proximal convoluted tubule (PCT) of the kidney cortex in the early-stage samples of diabetic nephropathy. Most target genes, such as HBA1, HBA2, HBB, and PEA15, did not exhibit strong signals. Pharmacological results implicate Baicalein, ferulic acid, and estradiol are potential natural regulatory compounds for PEA15 and TFPI2. AC1L3PBJ (PubChem CID: 118701068), honokiol, resveratrol, and vinblastine are candidate regulatory compounds for hemoglobin subunits. These findings necessitate further validation through experimental and clinical studies, which may be instrumental in uncovering the underlying mechanisms of diabetic cardio-renal co-injury and facilitating drug discovery. •No shared genes between diabetic cardiomyopathy and nephropathy were identified before.•This study identified the pharmacological targets associated with diabetic complications.•Apoptosis and ferroptosis contribute to the co-injury of the diabetic heart and kidney.•Small molecule compounds that target shared genes and their TFs are potential drug candidates.